The Role of Beta Bank Sampah Community in Plastic Waste Management in Hative Besar Village, Ambon City - Kappy, Tresia M; Maimina, Steiven; Latue, Philia Christi; Rakuasa, Heinrich (Yayasan Sinergi Kawula Muda, 2023)
In accordance with the provisions of Law No. 18/2008 on Waste Management, it is now necessary to change the way people view waste and how they treat or manage waste. For alternative solutions to the waste problem, the development of waste banks is a social engineering activity that teaches people to sort waste and fosters public awareness in waste management. The purpose of this study was to determine the role of Beta Waste Bank in managing plastic waste in Hative Besar Village, Teluk Ambon Sub-district, Ambon City. The type of research used in this research is descriptive qualitative. This research involves collecting data about the role of Beta Bank Sampah in managing plastic waste in Hative Besar Village, Teluk Ambon Subdistrict, Ambon City, the location of this research is Hative Besar Village, Teluk Ambon Subdistrict, Ambon City. The subjects in this study were the founders of Beta Bank Sampah and the customers of Beta Bank Sampah, totaling 12 people. The variable in this study uses a single variable, namely the waste bank manager. However, the single variable will be described with reference to the LH parliament No. 13 of 2012. In this study researchers used several data collection techniques, namely, observation, interviews, questionnaires and documentation. Based on the results of the research conducted, Beta Bank Sampah is a community that is actively engaged in efforts to maintain environmental balance by carrying out the process of recycling plastic waste into creations of economic value. good awareness efforts on environmental cleanliness especially on the impact of the threat of plastic waste that grows with the growth rate of society. and Beta Bank Sampah has helped the city government in realizing the clean Ambon program by reducing the use of plastic waste in people's lives.